The LIFE certification methodology as a diagnostic tool of the environmental management system of the automotive industry - Reale, Ricardo; Ribas, Luiz César [UNESP]; Borsato, Regiane; Magro, Teresa Cristina; Voigtlaender, Maureen (Elsevier, 2016)
We conducted a diagnosis of the environmental management system of the Brazilian auto parts industry, using the LIFE certification methodology (lasting initiative for earth) as a diagnostic tool. This certification recognizes enterprises that develop conservation actions for biodiversity for the purpose of minimizing and/or mitigating their own negative impact on the environment. Through this method, it was possible to quantify and qualify the environmental impact and investigate the existence of conservation actions, as well as evaluate them quantitatively and qualitatively. Therefore, we used this methodology to demonstrate its potential as an economic instrument of environmental management through its application within an EMS certified to the ISO 14001 series. It was shown that there are many benefits of using sustainable environmental resources (possibility to return to ISE-Corporate Sustainability Index-Bovespa) and for the final disposal of waste from production. The main results indicated that the LIFE methodology allows companies to incorporate actions to biodiversity conservation transversally into their EMSs, which can increase the efficiency of enterprise management. We believe that the use of this management model by other companies will enable the intensification of conservation actions in protected areas in their regions.
Keywords: Biodiversity; Conservation; Economy; Environmental management; LIFE certification; Mitigation of impacts